The first directors of Vienna Josephinum - Ioannis Alexander von Brambilla and Franz Anton Brendel von Sternburg - Habek, Dubravko; Habek, Roko; Hrgović, Zlatko (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2024)
On November 7, 1785, Emperor Joseph II opened a medical-surgical academy in Vienna named after him Josephinum for the academic training of surgeons and doctors. The first director of the academy was Ioannis Alexander von Brambilla (1728-1800), responsible for the academization of surgeon training, who organized numerous instruments and the Josephinum library. His successor was Franz Anton Brendel von Sternburg (1723-1803) who, in addition to his professional and teaching work at the academy, founded a foundation that lasted until the First World War. In addition to the above information, we have presented recent insights from their private lives and completed their famous biographies. The first two directors of the Josephinum worked at the time of the “first Viennese medical school”, which, with Enlightenment ideas, directly participated in the academization of surgery and the transformation of pre-modern medicine into modern medicine.